Point-contact Andreev-reflection spectroscopy in anisotropic superconductors: the importance of directionality (Review Article) - Daghero, D.; Tortello, M.; Pecchio, P.; Stepanov, V.A.; Gonnelli, R.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Point-contact Andreev-reflection spectroscopy (PCARS) has demonstrated to be one of the most effective experimental tools for the investigation of fundamental properties of superconductors such as the superconducting gap and the electron–phonon (or, more generally, electron–boson) coupling. By reviewing relevant examples reported in literature and presenting new results, in this paper we show that when the direction of the interface with respect to the crystallographic axes can be controlled (as in single crystals and epitaxial films) PCARS can provide invaluable information about the anisotropy of the pairing wavefunction or — in the case of multiband superconductors — on the number, amplitude and symmetry of the energy gaps. Moreover, the analysis of PCARS results within a suitable 3D generalization of the BTK model allows obtaining qualitative information about the topology of the Fermi surface.